Status and Assessment Method of Nuclear Safety Analysis Software in China - Gao, Xinli; Jing, Jianping; Han, Xiangzhen; Jia, Bin; Tian, Xinlu; Liu, Fudong; Zhang, Chunming (Frontiers in Energy Research, 2021)
In recent years, China’s nuclear power industry has enjoyed a good momentum of development, and related companies have also developed many nuclear analysis software applications. However, as the National Nuclear Safety Administration (NNSA, Chinese nuclear regulatory institution) did not approve any software before 2018, all these software applications were not evaluated formally, so they have not yet been used in reactor safety analysis. In order to solve this problem, in 2018, the National Nuclear Safety Administration started to carry out an engineering applicability evaluation for software developed by Chinese companies. After several years of review, as the first approved Chinese domestic software, core physics analysis software PCM developed by the China General Nuclear Power Group officially passed the software safety evaluation of the China Nuclear Safety Administration. This study will present the basic situation of the development of China’s nuclear power engineering software and introduce the framework, methods, procedures, requirements, and other aspects of China’s software safety evaluation work. The evaluation process and evaluation key issues of PCM software will also be illustrated.